Digital Platforms' Responsibility for the Security of Users' Personal Data: A Juridical Analysis - Khuan, Hendri; Paminto, Saptaning Ruju; Fadhilah, Nurul (Ipso Jure, 2025)
The rapid development of information technology has created a complex and widespread digital ecosystem, where digital platforms are becoming massive collectors of personal data. This phenomenon poses a risk of data leakage and misuse that threatens individual privacy. In Indonesia, even though Law No. 27 of 2022 concerning Personal Data Protection (PDP Law) has been passed, its implementation still faces significant challenges, especially related to infrastructure readiness, law enforcement, and public awareness. Existing regulations tend to be normative and have not been able to keep up with rapid technological innovation, so the responsibility of digital platforms in maintaining data security is still weak and formalistic. This study uses a normative juridical approach to examine the effectiveness of the PDP Law in regulating the legal responsibilities of digital platforms. The results of the analysis show the need to strengthen supervision mechanisms, firm law enforcement, and increase technical capacity and human resources. Lessons learned from international standards emphasize the importance of independent oversight bodies and the application of privacy by design principles. With the synergy of adaptive regulations, reliable technology, and collective awareness, personal data protection can be realized effectively to protect users' rights and security in the digital era.